2009
DOI: 10.2355/isijinternational.49.1588
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Stainless Steel Component Manufactured by Shaped Metal Deposition

Abstract: Fig. 4. OM; top part; vertically oriented vermicular ferrite (denoted as V) and areas of Widmanstätten austenite (W). Fig. 5.Tensile tests results of specimens taken from areas from 11 to 27 mm above the base plate with tensile direction perpendicular to the SMD deposition direction: ultimate tensile strength (UTS), 0.2 % yield strength (YS), and ductility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 21 publications
0
32
0
4
Order By: Relevance
“…на данный момент относительно немного публикаций посвящено проблеме аддитивного производства на основе электродуговой сварочной технологии. и хотя первые статьи посвященные электродуговой аддитивной наплавке появились в 1990-е годы [3,18], проблемы формирования структуры металла шва, проблемы, связанные с формообразованием шва в нестационарных усло-виях теплоотвода, остаются нерешенными и акту-альными [15,19].…”
Section: 9unclassified
See 2 more Smart Citations
“…на данный момент относительно немного публикаций посвящено проблеме аддитивного производства на основе электродуговой сварочной технологии. и хотя первые статьи посвященные электродуговой аддитивной наплавке появились в 1990-е годы [3,18], проблемы формирования структуры металла шва, проблемы, связанные с формообразованием шва в нестационарных усло-виях теплоотвода, остаются нерешенными и акту-альными [15,19].…”
Section: 9unclassified
“…авторы работы [19] проводили схожие ис-следования на аустенитной нержавеющей стали 308S93. при этом так же был изготовлен «короб» с длиной стенки 130×130 мм, с высотой стенки 31 мм, наращенной за 30 сварочных проходов, толщина стенки -8 мм.…”
Section: 9unclassified
See 1 more Smart Citation
“…At the moment, there are relatively few publications devoted to the AM problem based on arc welding technology. And though the first articles devoted to electric arc additive surfacing appeared in the 1990s [3,18], the problem of weld metal structure formation, and the problems associated with weld shaping under the non-stationary conditions of heat dissipation remain unsolved and relevant [15,19].…”
Section: D Additive Technologiesmentioning
confidence: 99%
“…It was shown that the process parameters such as laser power, traverse speed, and powder feed rate significantly affect the microstructure of the deposited parts and hence on their microhardness. The first attempt to use ASS in arc plus wire-based SMD process was by Skiba et al [12]. This work used non-pulsed current SMD process for manufacturing the test specimens.…”
Section: Introductionmentioning
confidence: 99%